Decrease in manganese superoxide dismutase leads to reduced root growth and affects tricarboxylic acid cycle flux and mitochondrial redox homeostasis. - Morgan, M; Lehmann, M; Schwarzländer, M; Baxter, C; Sienkiewicz-Porzucek, A; Williams, T; Schauer, N; Fernie, A; Fricker, M; Ratcliffe, R; Sweetlove, L; Finkemeier, I (2008)
Superoxide dismutases (SODs) are key components of the plant antioxidant defense system. While plastidic and cytosolic isoforms have been extensively studied, the importance of mitochondrial SOD at a cellular and whole-plant level has not been established. To address this, transgenic Arabidopsis (Arabidopsis thaliana) plants were generated in which expression of AtMSD1, encoding the mitochondrial manganese (Mn)SOD, was suppressed by antisense. The strongest antisense line showed retarded root growth even under control growth conditions. There was evidence for a specific disturbance of mitochondrial redox homeostasis in seedlings grown in liquid culture: a mitochondrially targeted redox-sensitive green fluorescent protein was significantly more oxidized in the MnSOD-antisense background. In contrast, there was no substantial change in oxidation of cytosolically targeted redox-sensitive green fluorescent protein, nor changes in antioxidant defense components. The consequences of altered mitochondrial redox status of seedlings were subtle with no widespread increase of mitochondrial protein carbonyls or inhibition of mitochondrial respiratory complexes. However, there were specific inhibitions of tricarboxylic acid (TCA) cycle enzymes (aconitase and isocitrate dehydrogenase) and an inhibition of TCA cycle flux in isolated mitochondria. Nevertheless, total respiratory CO2 output of seedlings was not decreased, suggesting that the inhibited TCA cycle enzymes can be bypassed. In older, soil-grown plants, redox perturbation was more pronounced with changes in the amount and/or redox poise of ascorbate and glutathione. Overall, the results demonstrate that reduced MnSOD affects mitochondrial redox balance and plant growth. The data also highlight the flexibility of plant metabolism with TCA cycle inhibition having little effect on overall respiratory rates.